2013
DOI: 10.1007/s13762-013-0376-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the physicochemical qualities of a typical rural-based river: ecological and public health implications

Abstract: The physicochemical qualities of a typical rural-based river were assessed over a 12-month period from August 2010 to July 2011 spanning the spring, summer, autumn and winter seasons. Water samples were collected from six sampling sites along Tyume River and analysed for total nitrogen, orthophosphate, biochemical oxygen demand (BOD), temperature, pH, dissolved oxygen (DO), electrical conductivity (EC), total dissolved solids (TDS) and turbidity. BOD regimes did not differ significantly between seasons and bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The increase in pH values of the stored water above sources could be as a result of the activities of the resident flora and or their death which results in the release of inorganic substances such as ammonia [39]. Changes in pH are known to be a resultant of processes such as photosynthesis, respiration, temperature exposure to air, disposal of industrial wastes, geology and mineral content of a catchment area, acid mine drainage, agricultural runoff, carbon dioxide concentration in the atmosphere, and accumulation and decomposition of organic detritus in the water producing weak carbonic acids that impact on pH [40]. Furthermore, the increase in the mean values of the DO (stored water) might be as a result of exposure of the containers to air during storage [41].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in pH values of the stored water above sources could be as a result of the activities of the resident flora and or their death which results in the release of inorganic substances such as ammonia [39]. Changes in pH are known to be a resultant of processes such as photosynthesis, respiration, temperature exposure to air, disposal of industrial wastes, geology and mineral content of a catchment area, acid mine drainage, agricultural runoff, carbon dioxide concentration in the atmosphere, and accumulation and decomposition of organic detritus in the water producing weak carbonic acids that impact on pH [40]. Furthermore, the increase in the mean values of the DO (stored water) might be as a result of exposure of the containers to air during storage [41].…”
Section: Discussionmentioning
confidence: 99%
“…These high water temperatures might increase the toxicity of such substances as ionized ammonia. In fact, ionized ammonia becomes the predominant form of ammonia in surface water when temperature is high (≥ 25°C) [16,17]. But this reaction also depends on the water's pH.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in water quantity during low flow increases the concentration of dissolved salts. These high values of electrical conductivity might damage aquatic life [17]. As far as Total [24] reported that high TDS concentrations may indicate existence of potentially harmful contaminants such as metals and other agricultural or industrial chemicals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy metals can accumulate in aquatic organisms, persist in water and find their way to human body through drinking water or via the food chain (Reyhani et al, 2013;Varol and Sen, 2012 Water quality in urban river systems is under increasing stress because of industrial and domestic wastewater effluents and agricultural runoff (Al Obaidy et al, 2014). Many rural citizens throughout the world tend to use river water for household needs and thus anthropogenic activities have threatened their water supply (Sibanda et al, 2014). The River Damavand running by the side of the Damavand City in Iran, receives municipal and industrial loads from its surrounding environment.…”
Section: Introductionmentioning
confidence: 99%